Development and validation of a protocol to determine product perception in relation to the moment of the day - M. Visalli; S. Plano; C. Tortorello; D. Vigo; M.V. Galmarini (MethodsX)
Chronotype refers to an individual's tendency to engage in activities either earlier or later, in alignment with the biological rhythm of their body and its interaction with the environmental cycle. Chronotypes influence food preferences and meal timing, yet most studies rely solely on questionnaires without integrating real-time tasting data. To address this gap, we developed and validated a method to measure sensory perception and examine its variations throughout the day in alignment with circadian rhythms. Fifty-two university students completed the Munich Chronotype Questionnaire and, over four days within a week, they participated in sensory evaluations using a web-based questionnaire. At four daily time slots (morning, midday, afternoon, evening), participants tasted candies and assessed some sensory attributes—sweetness, sourness, bitterness, freshness, and overall flavor—using the Rate-All-That-Apply method. Before each evaluation, they also reported their level of hunger, thirst, tiredness, and willingness to complete the task. Reminders were sent via pre-programmed messages to ensure adherence to the schedule. The results demonstrate the feasibility of the method, with low attrition rates and consistent participant motivation over the study period. Sensory perception was found to vary across the day and in relation to chronotype, highlighting the method's potential for advancing research in sensory chrononutrition. • A web-based questionnaire including tasting was developed to assess sensory perception at different times of the day over four days. • Perception was analyzed in relation to chronotype. • Face validity was confirmed, as significant variations based on chronotypes were observed.